Association of Fetal Abdominal-Head Circumference Size Difference With Shoulder Dystocia: A Multicenter Study - Loraine Endres; Emily DeFranco; Theresa Conyac; Marci Adams; Ying Zhou; Kristin Magner; Luke O'Rourke; Kiley A. Bernhard; Danish Siddiqui; Anna McCormick; Jacques Abramowicz; Ronald Merkel; et al. (Thieme Medical Publishers, Inc., 2015)
Abstract Objective This study aims to determine if shoulder dystocia is associated with a difference in the fetal abdominal (AC) to head circumference (HC) of 50 mm or more noted on antenatal ultrasound. Study Design A multicenter matched case-control study was performed comparing women who had shoulder dystocia to controls who did not. Women with vaginal births of live born nonanomalous singletons ≥ 36 weeks of gestation with an antenatal ultrasound within 4 weeks of delivery were included. Controls were matched for gestational age, route of delivery, and diabetes status. Results We identified 181 matched pairs. Only 5% of the fetuses had an AC to HC of ≥ 50 mm. The proportion of AC to HC difference of ≥ 50 mm was significantly higher in shoulder dystocia cases (8%) than controls (1%, p = 0.002). With multivariate regression, the three significant factors associated with shoulder dystocia were AC to HC ≥ 50 mm (odds ratio [OR], 7.3; confidence interval [CI], 1.6-33.3; p = 0.010), femur length (OR, 1.1; CI, 1.0-1.2; p = 0.002), and induced labor (OR, 1.8; CI, 1.1-3.1; p = 0.027). Conclusion A prenatal ultrasound finding of a difference in AC to HC of ≥ 50 mm while uncommon is associated with shoulder dystocia.